Women's Preventive Services Initiative's Well-Woman Chart: A Summary of Preventive Health Recommendations for Women. Issue 3 (September 2019) - Phipps, Maureen G.; Son, Sarah; Zahn, Christopher; O'Reilly, Nancy; Cantor, Amy; Frost, Jennifer; Gregory, Kimberly D.; Jones, Michelle; Kendig, Susan M.; Nelson, Heidi D.; Pappas, Miranda; Qaseem, Amir; et al.
Abstract : The Well-Woman Chart summarizes current recommendations for preventive health services for women from adolescence and continuing across the lifespan. It was developed by the Women's Preventive Services Initiative, a national collaborative of women's health professional organizations and patient representatives. The Well-Woman Chart includes current clinical guidelines from the U.S. Preventive Services Task Force, Bright Futures from the American Academy of Pediatrics, and the Women's Preventive Services Initiative that are covered with no cost-sharing for public and most private insurance plans under the prevention service mandate of the Affordable Care Act. The structure of the Well-Woman Chart is based on age intervals and pregnancy status categories that align with existing recommendations. The target audience for the Well-Woman Chart is all clinicians providing preventive health care for women, particularly in primary care settings, and patients affected by the recommendations. The preventive services recommendations apply to females 13 years of age and older and pregnant females of any age. The Well-Woman Chart provides clinical guidance for screening, counseling, and other recommended preventive services for women during health care visits based on age, pregnancy status, and risk factors. Abstract : "Recommendations for Well-Woman Care" is a well-woman chart that includes evidence-based clinical prevention service recommendations issued by the American Academy of Pediatrics' Bright Futures, the United States Preventive Services Task Force, and the Women's Preventive Services Initiative.